1992
DOI: 10.2337/diab.41.11.1496
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Analysis of Glucokinase Gene With NIDDM in Caucasian Pedigrees

Abstract: NIDDM has a strong genetic component, as evidenced by the high level of concordance between identical twins. The nature of the genetic predisposition has remained largely unknown. Recently, the glucokinase gene locus on chromosome 7p has been shown to be linked to a subtype of NIDDM known as MODY in French and British pedigrees, and glucokinase mutations have been identified. To study the relationship between the glucokinase gene and NIDDM, we performed a linkage analysis in 12 Caucasian pedigrees ascertained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Because of uncertainty as to the mode of inheritance, we have tested for linkage with type II diabetes in nuclear families under different model assumptions with the use of moderately low penetrance parameters (19). Pedigrees in which a negative LOD score is found, usually because of obligate recombinants, can be excluded from additional study.…”
Section: Discussionmentioning
confidence: 99%
“…Because of uncertainty as to the mode of inheritance, we have tested for linkage with type II diabetes in nuclear families under different model assumptions with the use of moderately low penetrance parameters (19). Pedigrees in which a negative LOD score is found, usually because of obligate recombinants, can be excluded from additional study.…”
Section: Discussionmentioning
confidence: 99%
“…The present study indicates that a dominant model is most applicable, but the possibility of a polygenic component implies that linkage analysis could model more than one locus; when a single locus model is used, lower penetrance parameters should be included [45,46]. The best fit model with COMDS gave a susceptibility gene frequency 7.4 % and the penetrance factors derived in this study may be applied to future linkage analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, the premature disease mortality and late-onset of this disease means that suitable pedigrees with one affected and one unaffected parent are unusual [47]. Thus, linkage analysis is most appropriate in pedigrees with specific monogenic disorders such as MODY [48,49] although it can be useful in excluding a major dominant gene effects in a series of NIDDM nuclear families [46]. If sufficient numbers of pedigrees are being studied, the two-locus model could be applied, although combined segregation and linkage analysis of plasma glucose levels and diabetes with candidate genes in a given data set is an alternative approach [38].…”
Section: Discussionmentioning
confidence: 99%
“…Froguel et al (45) found no evidence of linkage or evidence for mutations in 21 French NIDDM families. Both Cook et al (47) and our laboratory (48) failed to find linkage in Northern European families, and Janssen et al (42) reported no linkage in Pima Indians. Although Chiu et al suggested that glucokinase mutations were important in American blacks based on an association study (49), screening of this population did not identify important mutations (50).…”
Section: Glucokinase (Mody-2)mentioning
confidence: 92%